Exploring community willingness and barriers to digital solutions and training for dengue prevention: a cross-sectional study in major urban areas of Malaysia - Dom, Nazri Che; Dapari, Rahmat; Kamal, Husna Ahmad; Harun, Qamarul Nazri; Salleh, Siti Aekbal; Aljaafre, Ahmad Falah (BioMed Central, 2025)
Background: Dengue fever is a significant public health concern in urban Malaysia, driven by high population density and rapid urbanization. Effective prevention requires community engagement in both digital and training-based interventions. This study aims to evaluate the sociodemographic and perception-based factors associated with the willingness to adopt a dengue prevention application and participate in dengue prevention training programs in major urban areas of Malaysia. Methods: A cross-sectional study was conducted from February to May 2024 in four major urban areas of Malaysia; Selangor, Wilayah Persekutuan, Perak, and Johor selected due to their high dengue incidence rates, large urban populations, and active public health interventions. A multistage stratified random sampling method, followed by systematic random sampling at the household level, was used to select participants. A structured questionnaire was then administered to collect data on sociodemographic characteristics, perceptions of drone use, and willingness to adopt dengue prevention interventions. Descriptive and multinomial logistic regression analyses were performed to identify factors associated with willingness to adopt a dengue prevention application and participate in training programs. Results: A total of 261 respondents participated, with a mean age of 34.3 years (SD = 12.7). Younger respondents (< 40 years) were significantly more willing to participate in dengue prevention training (“Yes” vs. “No”: OR = 2.506, 95% CI: 1.074–5.847, p = 0.034), while age was not significantly associated with willingness to adopt the application. Respondents who held negative perceptions of drone use were significantly less likely to consider downloading the dengue prevention application (“Maybe” vs. “No”: OR = 0.237, 95% CI: 0.058–0.962, p = 0.044), indicating that mistrust or concerns about drone technology may act as a barrier to digital intervention adoption. Other factors, including gender, duration of residence, housing type, and general concerns about drone use, were not significantly associated with willingness to engage in either intervention. Conclusions: Younger age was associated with greater willingness to participate in dengue prevention training, while negative perceptions of drone use were linked to reduced likelihood of app adoption. Gender, duration of residence, and type of housing were not significantly associated with engagement. These findings suggest the potential value of targeted strategies that encourage youth involvement and address public concerns about drone technology to improve community participation in dengue prevention efforts in urban Malaysia.